Altered Functional Segregated Sensorimotor, Associative, and Limbic Cortical-Striatal Connections in Parkinson's Disease: An fMRI Investigation - Mi, Tao-Mian; Zhang, Wei; Li, Yu; Liu, Ai-Ping; Ren, Zhi-Li; Chan, Piu (Frontiers in Neurology, 2021)
Multiple studies have identified segregated functional territories in the basal ganglia for the control of goal-directed and habitual actions. It has been suggested that in PD, preferential loss of dopamine in the posterior putamen may cause a major deficit in habitual control (mediated by the sensorimotor cortical-striatal loop), and the patients may therefore be forced into a progressive reliance on the goal-directed behavior (regulated by the associative cortical-striatal loop). Functional evidence supporting this point is scarce at present. This study aims to verify the functional connectivity changes within the sensorimotor, associative and limbic cortical-striatal loops in PD. Resting-state fMRI of 70 PD patients and 30 controls were collected. Bilateral tripartite functional territories of basal ganglia and their associated cortical structures were chosen as regions of interest, including ventral striatum and ventromedial prefrontal cortex for limbic loop; dorsomedial striatum and dorsolateral prefrontal cortex for associative loop; dorsolateral striatum and sensorimotor cortex for sensorimotor loop. Pearson's correlation coefficients for each seed pair were calculated to obtain the functional connectivity. The relationships between functional connectivity and disease severity were further investigated. Functional connectivity between dorsolateral striatum and sensorimotor cortex is decreased in PD patients, and postitively correlated with disease duration; whereas functional connectivity between dorsomedial striatum and dorsolateral prefrontal cortex did not increase, but actually decreased instead, and negatively correlated with disease duration. The functional connectivity within the sensorimotor loop is pathologically decreased in PD, while the altered connectivity within the associative loop may indicate a failed attempt to compensate for the loss of connectivity within the sensorimotor loop.